Screening for prostate cancer: what are the benefits ? - Murad Lesmana (Universa Medicina, 2012)
In men of advanced age, the epithelial cells of the prostate gland undergo substantial stress-associated changes that may result in DNA damage. The aging prostate gland acquires several cancer cell foci originating from special clonal transformation. Most of these foci never develop into clinically detectable cancer.